Paediatric endoscopy by adult gastroenterologists in Ile-Ife, Nigeria: A viable option to increase the access to paediatric endoscopy in low resource countries - Olusegun I Alatise; Henry Chineme Anyabolu; Oludayo Sowande; David Akinola (Wolters Kluwer Medknow Publications, 2015)
Background: Paediatric endoscopy performed by adult gastroenterologists is a service delivery model that increases the access of children to endoscopy in countries where paediatric gastroenterologists with endoscopy skills are scarce. However, studies on the usefulness of this model in Nigeria and Sub-Saharan Africa are scarce. We aimed to evaluate the indications, procedures, diagnostic yield and safety of paediatric endoscopy performed by adult gastroenterologists in a Nigerian tertiary health facility. Materials and Methods: It was a retrospective study that evaluated the records of paediatric (≤18 years old) endoscopies carried out in the endoscopy suite of Obafemi Awolowo University Teaching Hospital Complex Ile-Ife, Nigeria from January 2007 to December 2014. Results: A total of 63 procedures were successfully completed in children of whom 4 were repeat procedures which were excluded. Thus, 59 endoscopies performed on children were analysed. Most (49; 83.1%) of these procedures on the children were diagnostic with oesophagogastroduodenoscopy being the commonest (43; 72.9%). Epigastric pain (22; 37.3%), haematemesis (17; 28.8%) and dysphagia (9; 15.3%) were the predominant indication for upper gastrointestinal (GI) endoscopy while haematochezia (9; 15.3%) and rectal protrusion (2; 3.4%) were the indications for colonoscopy. Injection sclerotherapy (3; 5.1%) and variceal banding (2; 3.4%) were the therapeutic upper GI endoscopic procedures conducted while polypectomies were performed during colonoscopy in 5 children (8.5%). Abnormal endoscopy findings were observed in 53 out of the 59 children making the positive diagnostic yield to be 89.8%. No complication, either from the procedure or anaesthesia was observed. Conclusion: Paediatric endoscopy performed by adult gastroenterologists is useful, feasible and safe. It is being encouraged as a viable option to fill the gap created by dearth of skilled paediatric gastroenterologists.